Hubungan Pembiasaan Shalat Dhuha dengan Akhlak Siswa Sekolah Menengah Atas - Indah Suci Sapitri (Program Pascasarjana Universitas Ibrahimy, 2020)
Islamic education has many objectives. It also includes the construction of students’ noble character. Students should be able to understand and be able to build a noble character with the dhuha prayer habituation. This study aims to determine how is the relationship between dhuha prayer habituation and the students’ morals in SMA Negeri 2 Kota Bogor. The method in this research used a quantitative approach. The data collection techniques in this research used questionnaires. The results of this research were with df in the amount of 77, with the value of r table at a significant level of 5%, these were known that r table 5% = 0.221. Therefore the research hypothesis stated that the Pearson Correlation (0.667)> r table (0.221). So that Ho was rejected and Ha was accepted by stating that there was a positive relationship between the practice of dhuha prayer and student morals, which is 44.5%.